(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This paper explores fundamental approaches to teaching the English language through the implementation of interactive methods. Interactive teaching strategies enhance learners’ engagement, promote communication, and foster critical thinking skills in language acquisition. The study examines techniques such as group discussions, role-playing, gamification, and technology-integrated activities, emphasizing their impact on improving learners’ language proficiency. Furthermore, it highlights the importance of creating a student-centered environment to facilitate active participation and collaborative learning. The findings suggest that interactive methods not only improve linguistic competence but also boost learners’ confidence and motivation, making the learning process more effective and enjoyable.